Exploring Muhammadiyah's Research Landscape: A Bibliometric Analysis and Emerging Trends - Muhamad Subhi Apriantoro; Ranu Diva Kaloka; Afief El Ashfahany; Hudaifah Hudaifah (Universitas Muhammadiyah Magelang, 2023)
This research aims to analyze the developmental map and direction of Muhammadiyah research using bibliometric studies to classify processed data based on author, year of publication, country of publication, and network analysis. Utilizing bibliometric analysis and quantitative methods from the Scopus database, 701 articles were collected, analyzed, and visualized. The majority of Muhammadiyah research authors are based in Indonesia. The most influential source is the Journal of Physics: Conference Series. Consequently, we identified four focal points of Muhammadiyah research, including (1) student learning, (2) Muhammadiyah and humanitarian issues, (3) Muhammadiyah human resources, and (4) Muhammadiyah research methods.